1991
DOI: 10.1021/j100178a038
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of excited-state intramolecular proton transfer in 1-(acylamino)anthraquinones

Abstract: The excited-state properties of 1-(acy1amino)anthraquinones have been examined using a variety of physical techniques, including static fluorescence spectroscopy, and picosecond and subpicosecond time-resolved fluorescence techniques, as well as picosecond transient absorption spectroscopy. The decay of the singlet excited states is dominated by a combination of efficient internal conversion via excited-state intramolecular proton transfer (ESIPT) and rapid intersystem crossing. For strongly electron withdrawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 2 publications
13
111
0
Order By: Relevance
“…. Most of the publications cited deal with derivatives of salicylic acid, its esters and amides, 18,[20][21][22][23][24][31][32][33]45 o-hydroxybenzaldehyde, acetophenone and related compounds, 19,38,41 o-hydroxybenzoxazoles, 21,42 benzothiazoles, 16,27,37 triazoles, 17,25,30,46 flavonols, 26,29,39,40 anthraquinones, [34][35][36] bipyridyls 28,47,49 and even such a simple model as malonic aldehyde. 48 There have also been several attempts to develop theoretical approaches for the connection between molecular structure and efficiency of ESIPT, for example, Nagaoka and Nagashima 'nodal planes.'…”
Section: Introductionmentioning
confidence: 99%
“…. Most of the publications cited deal with derivatives of salicylic acid, its esters and amides, 18,[20][21][22][23][24][31][32][33]45 o-hydroxybenzaldehyde, acetophenone and related compounds, 19,38,41 o-hydroxybenzoxazoles, 21,42 benzothiazoles, 16,27,37 triazoles, 17,25,30,46 flavonols, 26,29,39,40 anthraquinones, [34][35][36] bipyridyls 28,47,49 and even such a simple model as malonic aldehyde. 48 There have also been several attempts to develop theoretical approaches for the connection between molecular structure and efficiency of ESIPT, for example, Nagaoka and Nagashima 'nodal planes.'…”
Section: Introductionmentioning
confidence: 99%
“…13 An ESIPT time of 100-300 fs was noted, and tunneling of the localized proton nuclear wave packet was invoked to account for the fast proton transfer. Choi et al reported that ESIPT of 1-hydroxy-anthraquione (1-HAQ) in toluene occurs in 120 fs 18 (260 fs…”
Section: -18mentioning
confidence: 99%
“…The intensity of the orange fluorescence is half of the blue fluorescence intensity. The observation of the dual fluorescence is taken as strong indication to an excited state intramolecular proton transfer (ESIPT) [19][20][21][22][23]. Mostly, the excited-state (S 1 ) tautomer accessed by ESIPT has an energy comparable to or slightly less than that of the normal form, while the ground state (S 0 ) of the tautomer is of considerably higher energy.…”
Section: Scheme 1) Upon Performing Titration Measurements Of Carminimentioning
confidence: 99%